A Computational Model for Wildfire Propagation: The Case of Vale Natural Reserve - Viademonte, Sergio; Senna, Mariana; Carneiro, Nikolas; Bastos, Caio; Quadros, André; Almeida, Rodolfo (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2024)
This document describes a research project about the development and application of a wildfire propagation computational model, which simulates the occurrence and spread of wildfires in order to understand and predict their behaviour. The aim is to assist in the prevention, fighting and management of wildfires. It has been applied at Vale Natural Reserve (RNV) and Sooretama Biological Reserve (REBIO), in the State of Espírito Santo, southeast of Brazil. These reserves are a constant target for forest wildfires, and they represent approximately 13% of the remaining Atlantic Forest in the State of Espírito Santo. Initial results were obtained comparing three cases of observed wildfires with predicted area, which shows a satisfactory level of area agreement.